Prevalence of Growth Restriction at Birth for Newborns With Congenital Heart Defects: A Population-Based Prospective Cohort Study EPICARD - Ghanchi, Ali; Rahshenas, Makan; Bonnet, Damien; Derridj, Neil; LeLong, Nathalie; Salomon, Laurent J.; Goffinet, Francois; Khoshnood, Babak (Frontiers in Pediatrics, 2021)
Background and objectives: Congenital heart defects (CHD) and growth restriction at birth are two major causes of infant, childhood and adult morbidity and mortality. The aim of this study was to assess the overall risk of growth restriction at birth as measured by its imperfect proxy small (< 10th percentile) gestational age for newborns with isolated CHD (not associated with extra-cardiac anomalies), as well as, for five major specific CHD. Methods: Using data from a population-based cohort of children born with CHD, we assessed the risk of growth restriction at birth using SGA and severe SGA (3rd percentile). To compare the odds of SGA (< 10th percentile) and severe SGA (< 3rd percentile) across five specific isolated CHD, we used ordinal logistic regression using isolated, minor (non-operated) ventricular septal defect (VSD) as the control group. Results: The overall proportion of isolated CHD was 13% (95% CI, 12%-15%), which is approximately 30% higher than what would be expected in the general population; the risk of severe SGA was 5% (95% CI, 4%-6%). The five specific CHD had substantial differences in the risk of both SGA and more so severe SGA. The highest risk of SGA was for Tetralogy of Fallot (adjusted OR 2.7, 95% CI, 1.3-5.8) and operated VSD (adjusted OR 2.1, 95% CI, 1.1-3.8) as compared with the reference group of isolated, minor (non-operated) VSD. Conclusion: The overall risk of both SGA and severe SGA was higher in isolated CHD with substantial differences across the subtypes of CHD. These results may provide a clue for understanding the underlying mechanisms of the relation between alternations in fetal circulation associated with different types of CHD.